A swarm intelligent approach for multi-objective optimization of compact heat exchangers - Yousefi M.; Yousefi M.; Martins Ferreira R.P.; Darus A.N. (SAGE Publications Ltd, 2023)
Constrained optimization; Genetic algorithms; Heat exchangers; Pareto principle; Particle swarm optimization (PSO); Compact heat exchanger; Constraint handling strategies; Constraints handling; Multi objective algorithm; Non-dominated sorting genetic algorithm - ii; Trial-and-error procedures; Trial-and-error process; Weighted sum approaches; Multiobjective optimization